Automating the OEE Measurement in TPM Implementation Process - Mesquita, Rui Pedro Caseiro; Romana, Fernando Acabado; Gestoso, Carlos Guillen (Archives of Business Research, 2022)
This article is the result of a project in a reference company in the aviation sector in Portugal in its department of strategy and continuous improvement. The aim of the project was the implementation of the Total Productive Maintenance (TPM) philosophy at a corporate level. The pilot equipment for the implementation is in an aircraft structures production unit and preforms the initial machining of simple metal parts. For the implementation of the philosophy, indicators for monitoring the production process were integrated into the equipment, as well as the management of all the deliverables necessary for the operation in the philosophy of autonomous maintenance. Finally, the course of the entire process is analysed, improvements are suggested for the following equipment and the gains in production are identified.